Characterization of Indigenous Chicken Production System in Sheka Zone, South Western Ethiopia - Assefa, Hailu; Melesse, Aberra; Taye, Mestawet (International Journal For Research In Agricultural And Food Science, 2019)
The survey was conducted in Sheka Zone to characterize production system of indigenous chicken populations. Purposive random sampling technique was used to collect the data. Indigenous chicken production system data were assessed through semi-structured questionnaire survey. Households who rear only indigenous chicken were considered in this study. The findings revealed that mean flock size in the study area was 13.2 per household. This study revealed that the main source of stock to start chicken production was purchasing and gift. The culling practice, and disease and predation incidence in the area forces the activity of flock replacement which was 38.3 and 61.7% of respondents replaces their flock through buying from market and from hatched, respectively. The primary purpose of egg production in the study zone was for income generation (80.4%) and rear chickens mainly for breeding purpose to produce birds for flock replacement (50.4%). The study indicated that indigenous chicken production system in study area is characterized by scavenging with seasonal feed supplemented system. The most common supplementary feed was Enset Ventricosum (processed enset) (64.9%) in the study zone. The 52.5% of respondents keep their chickens in a separate house while the rest (47.5%) used different types of night sheltering systems. Newcastle disease (NCD) (40.5%) was the main devastating diseases in the study area. The mean age of maturity at first egg laying for pullets and sexual maturity for cockerels was 6.3 and 5.6 months, respectively. The result showed that the total number of 13.6 eggs per clutch and 3.0 clutches per year resulting in 40.8 eggs per year. The 8.7 eggs were incubated per clutch from which 74.1% hatched while survival rate was 59.3 %. Therefore, the present study suggests that indigenous chicken populations might possess useful genetic potentials for improved productivity under scavenging feed resource-based production systems.